China's new regional responsiveness: passive agency and counter-agency in processes of democratic transitions in Asia. Issue 1 (2nd January 2021) - Noesselt, Nele
ABSTRACT: This article undertakes a critical reassessment of the "black knight" role associated with the People's Republic of China in connection with recent processes of democratic decline in and beyond Asia. The time frame covered are the years 2013 to early 2020. In 2013, China officially launched its New Silk Road initiative, building cross-continental connectivity networks and trans-regional trade corridors. The internal stability of states along this New Silk Road is of crucial importance for the realization of Beijing's ambitious plan. How, then, does China view and interpret regime (trans)formations in its immediate neighbourhood? Is there any robust evidence for intentional agency (or counter-agency) of China in these processes? The article examines three case studies of "democratic regression" and "autocratic hardening" in Southeast Asia (Indonesia, Myanmar, Cambodia) and compares the findings to China's special relationship with Vietnam – like China a socialist one-party state.